Little Women - Alcott, Louisa May (Madhuban Educational Books New Delhi, 1982)
Louisa May Alcott wrote Little Women in two parts, each resoundingly popular and receiving critical acclaim. The novel follows the lives of the four March sisters, Meg, Jo, Beth and Amy, from childhood into maturity. The journey is not an easy one, and each is humbled and ultimately uplifted by her encounters with love, society and death. The work is based loosely on Alcott's experiences growing up with three sisters
Keywords: Children's Literature - Fiction